Feasibility and agreement between TTE and intracavitary ECG for PICC tip positioning in adult oncology patients: A single-centre exploratory study - Kai Xin; Mian Zhou; Yubiao Kang; Shanping Li; Chenjuan Wang; Lin Wang; Ling Yuan; Baorui Liu (PLoS ONE, 2026)
Background ECG-guided tip localization of central venous access has been clinically proven to be highly accurate and safe. However, real-time tip localization in patients with atrial fibrillation remains a challenge. Transthoracic ultrasound catheter tip localization is noninvasive and real-time. However, no methodological or accuracy studies of its localization have been reported in the literature. Objective To explore the accuracy of the TTE technique in localizing the tip position of central venous access devices (CVADs) and to establish a standardized TTE-guided catheter tip positioning procedure. Methods This was an self-controlled trial. A total of 35 patients requiring PORT or PICC implantation participated in this study from April 2023 to March 2024. First, catheter positioning was performed under TTE guidance, and after determining the position of the catheter tip, the insertion depth and relative data were recorded. Subsequently, ECG-guided positioning was performed. The final position of the catheter was standardized by ECG. Results A total of 35 patients successfully underwent CVAD insertion under the guidance of IC-ECG. Five patients were excluded from the per-protocol (PP) analysis because the catheter tip could not be visualized in the Apical Four Chamber View. Statistical analysis showed no significant difference between ECG-measured depth and TTE-measured depth (t = −1.405, p = 0.17). In the PP Bland–Altman analysis, the mean bias was −0.13 with 95% limits of agreement (LOA) from −1.10 to 0.83, indicating good agreement between the two methods. An additional intention-to-diagnose (ITD) analysis with extreme value imputation for the five missing cases yielded a mean bias of −0.34 and 95% LOA from −1.70 to 1.00, further confirming the robustness of the findings. The pain intensity score did not exceed 4 points for 34 patients, with only one patient reaching 5 points. The TTE operation time did not exceed 8 minutes for each patient. Conclusion This study suggests that non-contrast TTE shows reasonable consistency with IC-ECG, with short operation time and acceptable patient discomfort. TTE may serve as a feasible, real-time, non-invasive alternative for patients in whom IC-ECG cannot be used.